O uso do mobile banking na cidade de Araguaína - TO. - Drumond, Amannda Abreu (Universidade Federal do Tocantins, 2020)
Taking into account investments made in T.I. that occurred in the banking sector in recent decades and because of the complexity in technology adoption by users, this study seeks to examine the use of mobile banking in the city of araguaina-TO. Participants were 85 users using the banking application in Araguaína/TO. As a tool for data collection was used an auto filling questionnaire, composed of five scales that measured the search variables: expectation of effort, expectation of performance, social influence and enabling conditions. This present research proposes to introduce, interpret and discuss the relationships between variables, as well as test the hypotheses concerning the conceptual model proposed, through a transversal nature research with quantitative approach, whose collected data were analyzed by application of parametric statistic techniques calculations of descriptive statistics: averages, standard deviation and correlations; multivariate statistical calculations: multiple linear regressions analysis by method (hierarchical through software SPSS, version 22.0). The results obtained showed that the variablesproposed by Venkatesh (2003) have positive impact on the attitude to use mobile banking. Finally, this study showed that the attitude of the using of mobile banking, are influenced by expectation of effort, social influences and enabling conditions.